Guidelines for Neuroprognostication in Critically Ill Adults with Intracerebral Hemorrhage - Hwang, David Y.; Kim, Keri S.; Muehlschlegel, Susanne; Wartenberg, Katja E.; Rajajee, Venkatakrishna; Alexander, Sheila A.; Busl, Katharina M.; Creutzfeldt, Claire J.; Fontaine, Gabriel V.; Hocker, Sara E.; Madzar, Dominik; Mahanes, Dea; et al. (Neurocritical Care, 2023)
Background: The objective of this document is to provide recommendations on the formal reliability of major clinical predictors often associated with intracerebral hemorrhage (ICH) neuroprognostication. Methods: A narrative systematic review was completed using the Grading of Recommendations Assessment, Development, and Evaluation methodology and the Population, Intervention, Comparator, Outcome, Timing, Setting questions. Predictors, which included both individual clinical variables and prediction models, were selected based on clinical relevance and attention in the literature. Following construction of the evidence profile and summary of findings, recommendations were based on Grading of Recommendations Assessment, Development, and Evaluation criteria. Good practice statements addressed essential principles of neuroprognostication that could not be framed in the Population, Intervention, Comparator, Outcome, Timing, Setting format. Results: Six candidate clinical variables and two clinical grading scales (the original ICH score and maximally treated ICH score) were selected for recommendation creation. A total of 347 articles out of 10,751 articles screened met our eligibility criteria. Consensus statements of good practice included deferring neuroprognostication—aside from the most clinically devastated patients—for at least the first 48–72 h of intensive care unit admission; understanding what outcomes would have been most valued by the patient; and counseling of patients and surrogates whose ultimate neurological recovery may occur over a variable period of time. Although many clinical variables and grading scales are associated with ICH poor outcome, no clinical variable alone or sole clinical grading scale was suggested by the panel as currently being reliable by itself for use in counseling patients with ICH and their surrogates, regarding functional outcome at 3 months and beyond or 30-day mortality. Conclusions: These guidelines provide recommendations on the formal reliability of predictors of poor outcome in the context of counseling patients with ICH and surrogates and suggest broad principles of neuroprognostication. Clinicians formulating their judgments of prognosis for patients with ICH should avoid anchoring bias based solely on any one clinical variable or published clinical grading scale.
CRIS-Team Scopus Importer:2023-11-17
Keywords: Cerebral hemorrhage; Counseling; Critical care outcomes; Hemorrhagic stroke; Mortality; Patient outcome assessment; Practice guideline; Prognosis; Shared decision making